2017
DOI: 10.1016/j.celrep.2017.07.046
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of RNA Polymerase II Pausing and Bivalent Histone H3 Methylation during Neuronal Differentiation in Brain Development

Abstract: Summary During cellular differentiation, genes important for differentiation are expected to be silent in stem/progenitor cells yet can be readily activated. RNA polymerase II (Pol II) pausing and bivalent chromatin marks are two paradigms suited for establishing such a poised state of gene expression, however, their specific contributions in development are not well understood. Here, we characterized Pol II pausing and H3K4me3/H3K27me3 marks in neural progenitor cells (NPCs) and their daughter neurons purifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 48 publications
2
40
0
Order By: Relevance
“…A recent study by Liu J et al [ 54 ] looked at the developmental changes of the bivalent chromatin marks and paused Pol II during neuronal differentiation in the mouse brain, and noted in agreement to our study that genes involved in cell cycle and other catabolic processes show very high RNA pol II pausing. Unlike our study, Liu J et al [ 54 ] noted that bivalent marks primed neuronal specification genes for activation during differentiation. One of the possible reasons for the discrepancy might be that the data collected for eight cell types from public domain in this study does not have a well-defined developmental trajectory as during neuronal differentiation.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study by Liu J et al [ 54 ] looked at the developmental changes of the bivalent chromatin marks and paused Pol II during neuronal differentiation in the mouse brain, and noted in agreement to our study that genes involved in cell cycle and other catabolic processes show very high RNA pol II pausing. Unlike our study, Liu J et al [ 54 ] noted that bivalent marks primed neuronal specification genes for activation during differentiation. One of the possible reasons for the discrepancy might be that the data collected for eight cell types from public domain in this study does not have a well-defined developmental trajectory as during neuronal differentiation.…”
Section: Discussionsupporting
confidence: 92%
“…RNA Polymerase II (RNAPII) pausing at genes that are highly inducible has been hypothesized to play a pivotal role in preparing genes for rapid induction in response to environmental or developmental stimuli. In a number of mammalian cellular contexts, bivalent genes have been shown to have a high density of paused RNA Pol II at the promoter-proximal region compared to genes which are actively transcribed, therefore allowing genes to be maintained in a transcriptionally poised state (Stock et al 2007; Ferrai et al 2017; Liu et al 2017). Paused RNA Pol II can be distinguished from other forms by a phosphorylation at Ser5 (Ser5P) of the YSPTSPS heptad repeat at the C-terminus of the largest subunit of the Pol II complex.…”
Section: Resultsmentioning
confidence: 99%
“…S3B). Thus, in line with bivalent genes in other cell types (Liu et al, 2017;Williams et al, 2015), RNAPII pausing may not be a central mechanism in the later activation of Kmt2b-target genes in the germline.…”
Section: Bivalent and Monovalent Promoters Are Suppressed By Distinctmentioning
confidence: 99%
“…All the PRC1 components examined (Scml2, Rnf2 and Bmi1) and H2AK119ub were enriched at the bivalent, but not at the monovalent, promoters. In ESCs, RNA polymerase II (RNAPII) pausing has been suggested to be involved in priming of bivalent promoters (Marks et al, 2012;Stock et al, 2007), but recent reports have shown contrasting evidence (Liu et al, 2017;Williams et al, 2015). We investigated this possibility by analyzing the RNAPII enrichment using RNAPII ChIP-seq data in GSCs and found that RNAPII was not highly enriched at bivalent and monovalent TSSs compared with all H3K4me3-marked TSSs (Fig.…”
Section: Bivalent and Monovalent Promoters Are Suppressed By Distinctmentioning
confidence: 99%